Fc receptors are key discriminatory markers of granulocytes subsets in people living with HIV-1 - Marsile-Medun, Soledad; Souchard, Manon; Abba Moussa, Daouda; Reynaud, Élisa; Tuaillon, Edouard; Naranjo-Gomez, Mar; Pelegrin, Mireia (Frontiers in Immunology, 2024)
Granulocytes are innate immune cells that play a key role in pathogen elimination. Recent studies revealed the diversity of granulocytes in terms of phenotype and function. In particular, a subset of granulocytes identified as low-density granulocytes (LDG) has been described in physiological condition and with increased frequencies in several pathological contexts. However, the properties of LDG are still controversial as they vary according to the pathophysiological environment. Here we investigated the heterogeneity of granulocyte populations and the potential differences in phenotype and immunomodulatory capacity between LDG and normal density granulocytes (NDG) in people living with HIV-1 (PLWH). To this end, we developed an optimized method to purify LDG and NDG from a single blood sample, and performed in-depth, comparative phenotypic characterization of both granulocyte subtypes. We also assessed the impact of purification steps on the expression of cell surface markers on LDG by immunophenotyping them at different stages of isolation. We identified 9 cell surface markers (CD16, CD32, CD89, CD62L, CD177, CD31, CD10, CXCR4 and CD172) differentially expressed between LDG and NDG. Noteworthy, markers that distinguish the two subsets include receptors for the Fc part of IgG (CD16, CD32) and IgA (CD89). Importantly, we also highlighted that the purification procedure affects the expression of several cell surface markers (i.e.CD63, CD66b, …) which must be taken into account when characterizing LDG. Our work sheds new light on the properties of LDG in PLWH and provides an extensive characterization of this granulocyte subset in which Fc receptors are key discriminatory markers.